Serum Levels of Adipokines in Patients with Chronic HCV Infection: Relationship with Steatosis and Fibrosis - ÇELİKEL, ÇİĞDEM; EREN, FATİH; ATUĞ, ÖZLEN; YILMAZ, YUSUF (ELSEVIER SCIENCE INC, 2009)
Background and Aims. Hepatic steatosis and fibrosis are common histological findings in patients with chronic hepatitis C virus (HCV) infection. In this study we sought to determine whether serum levels of three adipokines (leptin, adiponectin and resistin) show any biochemical correlation with hepatic steatosis and fibrosis in patients with chronic HCV infection. Methods. We examined a total of 51 patients with chronic HCV infection (22 males and 29 females, mean BMI: 27.4 +/- 5 kg/m(2)) and 24 healthy control subjects (10 males and 14 females, mean BMI: 23.2 +/- 3 kg/m(2)). Liver steatosis and fibrosis were scored on biopsies. Serum levels of leptin, adiponectin and resistin were determined by ELISA. Results. HCV genotypes were 1b in 41 patients (80.4%), 3a in three patients (5.9%), 2a in two patients (3.9%), 1 a in two patients (3.9%), 1 c in one patient (2%), and 2b in one patient (2%). Serum levels of leptin, resistin, and the leptin-to-adiponectin ratio were significantly higher in patients with chronic HCV infection than in controls. Steatosis and fibrosis were detected in 33.3% and 70.5% of chronic HCV patients, respectively. No significant association with serum adipokine levels and degree of steatosis was evident. Low serum levels of resistin were associated with the presence of fibrosis independently of potential confounders. Conclusions. Patients with chronic HCV infection display elevated levels of adipokines in their sera. Reduced concentrations of resistin may be a biochemical marker of fibrosis in this patient group. (C) 2009 IMSS. Published by Elsevier Inc.
Keywords: HCV infection; Steatosis; Fibrosis; Leptin; Adiponectin; Resistin; CHRONIC HEPATITIS-C; CHRONIC LIVER-DISEASES; PLASMA ADIPONECTIN; INSULIN-RESISTANCE; LEPTIN LEVELS; VIRUS; ASSOCIATION; PROGRESSION